Congenital fetal heart defect - an agreement between fetal echocardiography and autopsy findings - Pavlicek, Jan; Tauber, Zdenek; Klaskova, Eva; Cizkova, Katerina; Prochazka, Martin; Delongova, Patricie; Stefunko, Beata; Szotkovska, Iveta; Dvorackova, Jana; Gruszka, Tomas (Biomedical papers, 2020)
Aims: To determine the frequency of pregnancy terminations due to prenatal congenital heart defect (CHD) and assess the agreement fetal echocardiography (FECHO) and autopsy findings. Methods: The data were retrospectively assessed between 2008 and 2017 in a population of 116 698 live births. The correlations between the FECHO and autopsy findings were classified into five levels of agreement: complete, partial, altered diagnosis, disagreement, and unfeasible autopsy. Results: Totally, 293 CHDs were identified and 49% of families (143/293) decided to terminate the pregnancy. In 1% (2/143) of cases, the autopsy could not be performed, for the other 99% (141/143), the pathologist confirmed the presence of CHDs. Complete agreement between FECHO and autopsy was achieved in 85% (122/143). In 10% (14/143) of cases, the pathologist found minor findings, which were not described in the FECHO. In 4% (5/143) of cases, the pathologist changed the main diagnosis. Conclusion: Altogether, the results indicated that FECHO is a highly sensitive method for the prenatal detection of CHD but is incapable of detecting the complete spectrum of cardiac defects. Autopsies verified the diagnosis, confirmed the overall impairment in the fetus, and provided data for further counselling of the affected family.
Keywords: autopsy; fetal echocardiography; screening; termination of pregnancy; congenital heart defect; chromosomal aneuploidy